2006
DOI: 10.2337/db06-0225
|View full text |Cite
|
Sign up to set email alerts
|

A Haplotype-Based Analysis of the PTPN22 Locus in Type 1 Diabetes

Abstract: A recent addition to the list of widely confirmed type 1 diabetes risk loci is the PTPN22 gene encoding a lymphoidspecific phosphatase (Lyp). However, evidence supporting a role for PTPN22 in type 1 diabetes derives entirely from the study of just one coding single nucleotide polymorphism, 1858C/T. In the current study, the haplotype structure of the PTPN22 region was determined, and individual haplotypes were tested for association with type 1 diabetes in family-based tests. The 1858T risk allele occurred on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 48 publications
4
49
0
Order By: Relevance
“…These are Hipk1 and Bcl2l15, which have been demonstrated to be involved in apoptotic processes; the scaffolding protein Magi3, which participates in PTEN signaling; and the E3 ubiquitin-protein ligase Trim33, which negatively regulates TGF-b signaling. Of note, none of these 23 genes has been found to be associated with inflammatory and autoimmune conditions in humans (53,54). Because BCL2l15 has been reported to be in linkage disequilibrium with PTPN22 within the human syntenic region on chromosome 1, the coding region of this gene was sequenced in the parental strains.…”
Section: Discussionmentioning
confidence: 99%
“…These are Hipk1 and Bcl2l15, which have been demonstrated to be involved in apoptotic processes; the scaffolding protein Magi3, which participates in PTEN signaling; and the E3 ubiquitin-protein ligase Trim33, which negatively regulates TGF-b signaling. Of note, none of these 23 genes has been found to be associated with inflammatory and autoimmune conditions in humans (53,54). Because BCL2l15 has been reported to be in linkage disequilibrium with PTPN22 within the human syntenic region on chromosome 1, the coding region of this gene was sequenced in the parental strains.…”
Section: Discussionmentioning
confidence: 99%
“…rs689 (−23HphI variant, a surrogate for the subdivision of VNTR into class I [A] and III [T] alleles) and rs3842755, which also allows subdivision of class III into IIIA (C) and IIIB (A) alleles [29][30][31]. The SNP rs2476601 (also denoted 1858C/T) was genotyped in the PTPN22 gene [32,33]. Genotyping was performed by an allelic discrimination method (7900HT system; Applied Biosystems, Foster City, CA, USA).…”
Section: Hla-dqb1 Genotypingmentioning
confidence: 99%
“…After correcting the most associated additional SNP, there was no evidence of any additional independent effects (minimum uncorrected P ϭ 0.00854 for rs735074 located in the flanking linkage disequilibrium block; corrected P ϭ 0.243), including the previously associated MAGI3 SNP rs1343125 (22) (uncorrected P ϭ 0.907), the Japaneseassociated SNP rs2488457 (25) (uncorrected P ϭ 0.866), and the rheumatoid arthritis-associated SNP rs3789604 (24) (uncorrected P ϭ 0.401) ( Table 1; Supplementary Table 2). We genotyped an additional five SNPs with TaqMan because they were not covered by either GWA scan: two SNPs (rs1310182 and rs2488458) associated with rheumatoid arthritis from Carlton et al (24), the rare nsSNP (ss73688585/K750N) associated with type 1 diabetes from Onengut-Gumuscu et al (23), and two SNPs (rs3789608 and ss73688608) found from our resequencing. Although we found evidence for associations between type 1 diabetes and rs1310182 (P ϭ 9.33 ϫ 10 Ϫ13 ), rs2488458 (P ϭ 3.46 ϫ 10 Ϫ34 ), and ss73688608 (P ϭ 1.80 ϫ 10 Ϫ7 ), these results were not independent of rs2476601/Arg620Trp (uncorrected P ϭ 0.840, 0.343, and 0.702, respectively).…”
Section: Ptpn22 In Type 1 Diabetesmentioning
confidence: 99%
“…Functional studies suggest that the Trp 620 allele has gain-offunction, immunosuppressive effects compared with the more common allele Arg 620 (19 -21). However, there have been attempts to assess whether there are other variants that confer risk of disease that are independent of rs2476601/ Trp 620 (22,23). One of the largest studies thus far to characterize disease association with PTPN22 resequenced the coding regions of the gene in 48 North American individuals and genotyped 37 SNPs in or near PTPN22 in up to 1,136 rheumatoid arthritis case subjects and 1,797 control subjects (set 1: 475 case subjects and 475 control subjects; set 2: 661 case subjects and 1,322 control subjects) (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation